The Effectiveness of Guessing Word Learning Model Type towards the Elementary Students’ Natural Science Learning Outcomes - Aisyiyah, Siti; Soegeng, Ay.; Prima, Filia (International Journal of Elementary Education, 2020)
The low natural science learning outcomes of the students' grade IV of SD Negeri Kedungpucang Puworejo was caused by external and internal factors. Intern factors came from the students' side individuals and external factors came from the students' outside of individuals. The purpose of this study was to determine the effectiveness of the cooperative learning model that is guessing word towards the natural science learning outcomes of the elementary school students grade IV. The present research was quantitative research using a posttest as the design. The population of the research was the 40 students of IV grade which obtained through sampling. The data was obtained using observation, interview, test, and documentation. The analysis result obtained with t-test was t-count3,2062, with dk = (n1 + n2 – 2) = 20 + 20 – 2 = 38 and the significant level of 5% with price t(1/2α;38) was obtained t-table = 2,0244. Because t-count ≥ t-table is 3,2062 ≥ 2,02809 so H0 was rejected. In conclusion, the learning cooperation model of guessing words can improve the natural science learning outcomes of the students of IV grade. The implementation of the learning model will help the teachers to innovate the learning activity so the learning outcomes can be reached optimally based on the expectation.